Uncovering the Influence of Mosque Openness on Speech Intelligibility: A Simulation Study - Heruputra, Muhammad Harish; Widyarko, Widyarko; Susanto, Dalhar (Journal of Islamic Architecture, 2025)
Mosques, serving as places of worship for Muslims, require a high level of speech intelligibility to achieve the solemnity of worship. Due to rising urban temperatures, many mosques in tropical urban areas are transitioning from their previously open-designed condition, relying more on natural ventilation, to enclosed ones by leaning more on artificial ventilation. This study aims to understand the influence of space openness on speech intelligibility in mosques. Speech intelligibility measures how clear a voice is in a room and is measured by the speech transmission index (STI) method. This research utilizes the quantitative approach, integrating site observations, on-site measurements, and computational simulations. Focused on Masjid UI as the case study, the study simulates open and enclosed design configurations across three scenarios: full, half-full, and empty rooms. The results show that a mosque with an open design has a higher STI than a mosque with an enclosed design. However, the difference is insignificant due to several supporting factors in the existing condition, such as the square-shaped plan design with a pyramid dome, equal loudspeaker sound distribution, and a crowded worshippers’ condition.